Unlocking constitutional and administrative law - Ryan, Mark; Foster, Steve, 1955- (New York: Routledge, 2023)
'Unlocking Constitutional and Administrative Law provides an indispensable foundation in this core law curriculum subject, ensuring that you grasp the main concepts with ease. Containing accessible explanations in clear and precise terms that are easy to understand, it provides an excellent foundation for learning and revising Constitutional and Administrative Law. The information is clearly presented in a logical structure and the following features support learning, helping you to advance with confidence: - Clear aims and objectives at the beginning of each chapter set out the skills and knowledge you will need to get to grips with the subject - Key Facts summaries throughout each chapter allow you to progressively build and consolidate your knowledge - Diagrams to aid memory and understanding - Cases and judgments are highlighted to help you find them and add them to your notes quickly - End-of-chapter summaries provide a useful check-list for each topic - Frequent activities and self-test questions are included so you can put your knowledge into practice. - Glossary of legal terminology clarifies important definitions This edition has been fully updated to include discussion of recent changes, issues, and developments since the last edition, including an expanded section on Brexit, proposed changes to Judicial review, developments in Wales, Ireland and Scotland, recent Bills raising issues concerning the rule of law, and a new chapter on the constitutional impact of Covid-19'--
Introductory concepts -- Constitutions -- The nature of the British constitution -- The sources of the British constitution -- The separation of powers -- The rule of law -- Parliamentary sovereignty -- Parliament I : nature, functions and privilege -- Parliament II : the House of Commons -- Parliament III : the House of Lords -- The executive -- Executive/parliamentary relations -- The Judiciary -- The decentralisation of public power -- The European Union -- The European Convention on Human Rights -- The Human Rights Act 1998 -- Freedom of Speech -- Judicial review I (rationale and procedure) -- Judicial review II (grounds of review and remedies) -- Grievance mechanisms.
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: Constitutional law -- Great Britain; Great Britain -- Politics and government